Biological conservation of microbes - Rolston, Holmes, 1932-2025, speaker (Colorado State University. Libraries, 1989)
A talk by Holmes Rolston, III in the CSU Department of Microbiology on September 11, 1989. Environmental ethics is typically concerned with big stuff, bears, wolves, plants, wildfires, or insects. The Endangered Species act protects these, but does not mention microbes. There are concerns about microbes, in diseases, such as polio, or for patents, or fermenting. There are agricultural, industrial, medical uses. The usual list of reasons for preserving species are that they have aesthetic, ecological, educational, historical, recreational, or scientific value. Microbes can have ecological, historical, and scientific value. Often we do not know how much, at least not yet. Microbes in rare places, such as in the hot springs of Yellowstone, may bring clues about the origin of life. Respect for life includes microbes. For perhaps two-thirds of the history of Earth, all life was one-celled.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: microbes; endangered species; ecological; historical; scientific value; respect for life